Parkin overexpression modulates gut-microbiota composition during aging in Drosophila melanogaster - Sarghie, Larisa; Istvan, Paula; Aparicio, Ricardo; Walker, David W.; Tacutu, Robi; Surleac, Marius (Frontiers in Microbiology, 2025)
BackgroundThe gut microbiota plays a key role in host health during aging, influencing metabolism, immune function, and lifespan. In older individuals, the microbial community often becomes less diverse and more unstable, which can contribute to chronic inflammation and increased disease risk. Parkin, an E3 ubiquitin ligase, is known to extend lifespan when overexpressed in Drosophila melanogaster, but it's still unclear whether it also influences the gut microbiota during aging and whether this might contribute to its longevity effects.MethodsTo investigate this, we used an inducible genetic system to overexpress Parkin in adult D. melanogaster. Midguts were collected at four time points: days 10, 30, 45, and 60, and bacterial DNA was extracted for 16S rRNA amplicon sequencing to characterize microbiota composition and diversity. To assess the functional impact of these microbial communities, homogenates from Parkin-overexpressing and control flies were fed to germ-free wild-type recipients, followed by monitoring of lifespan and expression of antimicrobial peptides.Results and discussionParkin overexpression resulted in age-dependent changes in gut microbiota composition and diversity. Community structure shifted significantly, with more pronounced differences observed in older flies. When fed to germ-free wild-type flies, homogenates from middle-aged and old control flies reduced the median lifespan. In contrast, the microbiome from Parkin-overexpressing flies was more similar to that of young flies. It did not reduce median lifespan and did not trigger the proinflammatory response seen with the control microbiome. Our findings suggest that Parkin promotes a gut microbial environment that is more balanced and less inflammatory, which may support healthier aging.ConclusionThis study demonstrates that Parkin overexpression influences gut microbiota composition in a way that may be beneficial to host health during aging. The microbial communities associated with Parkin-overexpressing flies were not only distinct but also functionally advantageous, reducing immune activation and extending median lifespan in germ-free recipients. To our knowledge, this is the first study to use Parkin overexpression to explore potential Parkin-related changes in the gut microbial community, changes that were captured dynamically at four different stages of the D. melanogaster lifespan.